Effects of Spinal Cord Stimulation on Cardiac Sympathetic Nerve Activity in Patients with Heart Failure - Naar, Jan; Jaye, Deborah; Linde, Cecilia; Neužil, Petr; Doškář, Petr; Málek, Filip; Braunschweig, Frieder; Lund, Lars H; Mortensen, Lars; Linderoth, Bengt; Lind, Göran; Bone, Dianna; et al. (Pacing and clinical electrophysiology, 2017)
BACKGROUND: Spinal cord stimulation (SCS) reduces sympathetic activity in animal models of heart failure with reduced ejection fraction (HF) but limited data exist of SCS in patients with HF. The aim of the present study was to test the primary hypothesis that SCS reduces cardiac sympathetic nerve activity in HF patients. Secondary hypotheses were that SCS improves left ventricular function and dimension, exercise capacity, and clinical variables relevant to HF. METHODS: HF patients with a SCS device previously participating in the DEFEAT-HF trial were included in this crossover study with 6-week intervention periods (SCS-ON and SCS-OFF). SCS (50 Hz, 210-μs pulse duration, aiming at T2-T4 segments) was delivered for 12 hours daily. Indices of myocardial sympathetic neuronal function (heart-to-mediastinum ratio, HMR) and activity (washout rate, WR) were assessed using 123 I-metaiodobenzylguanidine (MIBG) scintigraphy. Echocardiography, exercise testing, and clinical data collection were also performed. RESULTS: We included 13 patients (65.3 ± 8.0 years, nine males) and MIBG scintigraphy data were available in 10. HMR was not different comparing SCS-ON (1.37 ± 0.16) and SCS-OFF (1.41 ± 0.21, P = 0.46). WR was also unchanged comparing SCS-ON (41.5 ± 5.3) and SCS-OFF (39.1 ± 5.8, P = 0.30). Similarly, average New York Heart Association class (2.4 ± 0.5 vs 2.3 ± 0.6, P = 0.34), quality of life score (24 ± 16 vs 24 ± 16, P = 0.94), and left ventricular dimension and function as well as exercise capacity were all unchanged comparing SCS-ON and SCS-OFF. CONCLUSION: In patients with HF, SCS (12 hours daily, targeting the T2-T4 segments of the spinal cord) does not appear to influence cardiac sympathetic neuronal activity or function as assessed by MIBG scintigraphy.
Keywords: senioři; imaging; výsledek terapie; mužské pohlaví; srdce; sympathetic nervous system; míšní stimulace; ženské pohlaví; Humans; srdeční selhání; Spinal Cord; Heart; spinal cord stimulation; sympatický nervový systém; Sympathetic Nervous System; Spinal Cord Stimulation; Female; Aged; heart failure; mícha; Treatment Outcome; Heart Failure; lidé; Male